Actividad física y calidad de vida en personas con enfermedad renal crónica (2019)
Background: Physical activity may improve quality of life in patients with chronic kidney disease. Aim: To assess the relationship between physical activity and quality of life in patients with Chronic Kidney Disease. Material and Methods: The Kidney Disease Quality of Life-36 (KDQOL-36) and the International Physical Activity questionnaire were answered by 130 patients with chronic kidney disease (74 women, 80 receiving renal substitution therapy). Sociodemographic variables were recorded. Results: Patients on renal substitution therapy with a time lapse since diagnosis of 0 to 6 months had higher levels of physical activity than those with longer time lapses (51.4 ± 12.5 and 34.6 ± 8.1 minutes respectively). Disease burden scores were lower among patients with renal substitution therapy. There was a direct correlation between levels of vigorous and moderate physical activity and the physical functioning dimension in the quality of life questionnaire for patients with more than 19 months of disease. The dimension general physical health was significantly associated with physical activity in women and patients with 7 to 18 months of diagnosis. The dimension disease burden was associated with physical activity in women, patients not receiving substitution therapy and those with 7 to 18 months of diagnosis. Conclusions: Moderate and vigorous physical activity is directly related to the dimensions physical functioning, the general perception of physical health and inversely related with the dimension burden of disease.